Peran Media Komunikasi Dalam Pembentukan Karakter Intelektual Di Dunia Pendidikan - Arcadius Benawa (Universitas Multimedia Nusantara, 2010)
Reality right now indicates that communication media grows continuously and move so fast. In fact our world becomes a big village or borderless because of communication media. It’s really true that communication media gives big and good contribution for education, but how far we realize that communication media used to built intellectual characters among the students and lecturers also? Kata Kunci: media communication, intellectual characters, education.